(–)-Nortrachelogenin from Partrinia scabiosaefolia elicits an apoptotic response in Candida albicans. Issue 3 (15th February 2016) - Lee, Heejeong; Woo, Eun-Rhan; Lee, Dong Gun
Abstract : This study analyzes the antifungal properties of (–)-nortrachelogenin and elucidates its mode of action against pathogenic fungi. We performed susceptibility tests against several pathogenic fungi and verified the absence of hemolysis against human erythrocytes. Its antifungal activity increased reactive oxygen species (ROS) in response to intracellular stress and increased concentrations of both intracellular and extracellular trehalose without causing hemolysis. In addition, a cell wall regeneration study indicated its action on the cytoplasmic membrane. A cell surface study using 3, 3 ′ -dipropylthiacarbocyanine iodide [DiSC3 (5)] and 1, 6-diphenyl-1, 3, 5-hexatriene (DPH) demonstrated dissipation of the cytoplasmic membrane at high concentrations. Our study revealed a disturbance in the membrane at higher concentrations and externalization of phosphatidylserine in a dose-dependent manner, affecting other intracellular responses. Furthermore, we investigated the late stage of apoptosis using TUNEL and 4 ′, 6-diamidino-2-phenylindole (DAPI) assays. (–)-Nortrachelogenin-treated cells underwent apoptosis which was triggered by mitochondrial dysfunction via depolarization of the mitochondrial membrane, release of cytochrome c and calcium ion signaling, resulting in the activation of metacaspases. Different concentrations of (–)-nortrachelogenin induced membrane disruption and caspase-dependent apoptosis. Abstract : Apoptosis and membrane disruption by (–)-nortrachelogenin was induced by different doses. Abstract :